Constructing Beliefs: Media, Identity, and Social Attitudes in the Digital Age - Subiantoro, Anjar (Indonesian Scientific Publication, 2025)
This narrative review investigates how various media forms influence social perception and the formation of attitudes, focusing on narrative persuasion, framing effects, identity construction, and cross-cultural implications. The study begins by situating the relevance of the topic within the broader landscape of media influence on individual and collective behavior, especially in the digital age. Using a structured narrative review search across Scopus, PubMed, and Google Scholar, literature was collected based on relevant keywords such as